FRI0214 Incidence of pancreatic autoantibodies in primary sjÖgren syndrome. (1st June 2001) - Aksu, K; Oder, G Altan; Kabasakal, Y; Keser, G; Inal, V; Isik, A; Cetinkalp, S; Doganavsargil, E
Abstract : Background: Primary Sjögren (SjS) syndrome is one of the prototypes of autoimmune diseases. Objectives: We aimed to work out the incidence of pancreatic autoantibodies in this disease. Methods: Seventy-six patients (F/M: 71/5, mean age: 49 ± 13 years) diagnosed as primary SjS syndrome according to the San Diego criteria between February 1997 and December 2000, have been included in the study. Twenty two, age matched (52 ± 10 years) female patients with secondary SjS due to rheumatoid arthritis were defined as the control group. Healthy control group included 22 age matched (F/M: 21/1) patients. Immunosuppressive drug usage, liver or renal failure were within the exclusion criteria. Serum samples for anti-insulin (AIA), islet (ICA) and anti-insulin receptor (IRA) antibodies were obtained from all patients after an 18 h fasting. Results: The incidence of anti-insulin antibody was found as 17%, while it was 7% and%17 for islet antibodies and anti-receptor antibodies, respectively (Table 1 ). These values were not statistically significant when compared with secondary SjS and healthy control groups (p > 0.05). Conclusion: Incidence of pancreatic auto-antibodies in primary SjS with observed hyperactivity of B cells, was not found statistically different when compared with patient and healthy control groups.